2008
DOI: 10.1017/s0007123408000173
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for the Study of Personality and Political Behaviour

Abstract: Variance in how citizens interact with the political world constitutes one of many classes of individual difference. Understanding the antecedents of this variance is the central objective for students of political behaviour, and researchers draw on numerous factors in addressing this task. Unfortunately, one potentially vital factor, personality, has received only sporadic attention in recent decades. Neglect of personality was understandable for many years, as psychological research on personality failed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
608
8
10

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 497 publications
(678 citation statements)
references
References 189 publications
32
608
8
10
Order By: Relevance
“…We begin with Conscientiousness, which previous research has found is related to overall conservative ideology (Carney et al 2008;Gosling, Rentfrow, and Swann 2003;Mondak and Halperin 2008;Stenner 2005, ch. 6; but see Hibbing 2007 andMehrabian 1996) and voting for conservative/right-wing candidates (Barbaranelli et al 2007;Caprara, Barbaranelli, and Zimbardo 1999;Caprara et al 2006;Rentfrow et al 2009;Schoen and Schumann 2007).…”
Section: Aggregate Predictions: Personality and Overall Economic Anmentioning
confidence: 99%
See 1 more Smart Citation
“…We begin with Conscientiousness, which previous research has found is related to overall conservative ideology (Carney et al 2008;Gosling, Rentfrow, and Swann 2003;Mondak and Halperin 2008;Stenner 2005, ch. 6; but see Hibbing 2007 andMehrabian 1996) and voting for conservative/right-wing candidates (Barbaranelli et al 2007;Caprara, Barbaranelli, and Zimbardo 1999;Caprara et al 2006;Rentfrow et al 2009;Schoen and Schumann 2007).…”
Section: Aggregate Predictions: Personality and Overall Economic Anmentioning
confidence: 99%
“…8), job satisfaction (Hogan and Holland 2003;Salgado 1997), alcohol and tobacco consumption (Paunonen and Ashton 2001), and physical and mental health (Goodwin and Friedman 2006). Although the Big Five personality traits have only recently begun to 2 Cognitive ability is the only psychological trait that is more stable through the life cycle than the Big Five (Caspi, Roberts, and Shiner 2005, 466-67). receive attention in political science, existing evidence suggests that they are significant predictors of political outcomes such as ideology and turnout (Gerber et al 2010b;Mondak and Halperin 2008). Indeed, the size of the effects of these traits rivals those of canonical predictors of political behavior that have been the subject of countless studies-such as education and income (Gerber et al 2010b).…”
mentioning
confidence: 99%
“…Because personality traits have been shown to be partially innate and are generally formed early on in life (Bouchard and McGue 2003;McCrae 1988, 1992), they may likely precede both types of trust. Indeed, recent studies have shown that social trust is influenced by personality, either in terms of the broader traits in the Big Five personality scheme-especially Agreeableness, Openness and Neuroticism Mondak and Halperin 2008)-or more specific facets such as optimism and a sense of control (Couch and Jones 1997;Uslaner 2002; see also Hirashi et al 2008;Oskarsson et al 2012). In fact, social trust has in itself been suggested to be a facet under the trait Agreeableness in the Big Five framework (cf.…”
Section: Causal or Confounded? The Relationship Between Institutionalmentioning
confidence: 99%
“…Our political-economic argument linking risk aversion and ideology sits alongside a larger literature that posits more and more possible links between basic individual characteristics, such as personality traits, and political ideology and behavior (see, e.g., Mondak and Halperin 2008;Vecchione and Caprara 2009;Gerber et al 2010;Mondak et al 2010;Morton, Tyran, and Wengstrom 2011). With respect to this literature, our main contribution is to develop a clear theoretical framework linking basic individual characteristics-in this case, aversion to risk-to political ideology.…”
Section: Introductionmentioning
confidence: 94%